1981
DOI: 10.1002/chin.198113343
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS OF 2,2′‐BIS(DIPHENYLPHOSPHINO)‐1,1′‐BINAPHTHYL (BINAP), AN ATROPISOMERIC CHIRAL BIS(TRIARYL)PHOSPHINE, AND ITS USE IN THE RHODIUM(I)‐CATALYZED ASYMMETRIC HYDROGENATION OF α‐(ACYLAMINO)ACRYLIC ACIDS

Abstract: Der Titelligand wird in seiner rac. Form (IIa) ausgehend vom Diol (I) über sein Dibromid, dessen Behandlung mit tert.‐Butyl‐Li und nachfolgender Umsetzung mit Chlorodiphenylphosphin dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Among the most powerful ligands for asymmetric catalysis are bidentate phosphine ligands like BINAP 1 or DUPHOS. 2 Recently, Reetz et al showed that excellent stereoselectivity in asymmetric hydrogenation can be achieved with monodentate phosphite ligands.…”
mentioning
confidence: 99%
“…Among the most powerful ligands for asymmetric catalysis are bidentate phosphine ligands like BINAP 1 or DUPHOS. 2 Recently, Reetz et al showed that excellent stereoselectivity in asymmetric hydrogenation can be achieved with monodentate phosphite ligands.…”
mentioning
confidence: 99%
“…Since Christie and Kenner reported the first detection of atropisomerism in 1922 (Christie and Kenner, 1922), axial chirality was found in a lot of natural products and pharmaceutical compounds as exemplified by michellamines (Manfredi et al, 1991;Bringmann et al, 1993) and vancomycin (Nicolaou et al, 1999). Besides, many chiral ligands and catalysts, such as BINOL, BINAP, and phosphoric acids, have been developed based on axially chiral biaryl scaffolds (Miyashita et al, 1980;Akutagawa, 1995;Kumobayashi et al, 2001;Brunel, 2005;Brunel, 2007;Genet et al, 2014). It is well-known that the enantiopurities of chiral ligands and catalysts are critical to their enantiocontrol, and atropisomers of bioactive molecules always exhibit different pharmacodynamic and pharmacokinetic behavior both in vivo and in vitro (Eichelbaum and Gross, 1996;Clayden et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2 Until now, various chiral backbones have been disclosed, among which the chiral atropoisomeric binaphthyl skeleton, 3 chiral spiro framework, 4 and planar-chiral ferrocene backbones 5 are among the most in-depth studied (Figure 1). These fundamental chiral frameworks have been successfully employed in the preparation of chiral ligands and organocatalysts, such as BINAP, 6 SDP, 7 JosiPhos, 7 and various CPAs, 8 which exhibit excellent catalytic performance in a wide range of reactions. In general, chiral ligands or catalysts bearing different backbones have dramatically different performances in catalytic reactions as a result of different stereo hindrances, bite angles, 9 or dihedral angles.…”
mentioning
confidence: 99%
“…BINOL, disclosed by Noyori,6,12 is the landmark application of the chiral atropoisomeric skeleton in asymmetric synthesis. Our group has also been actively investigating privileged chiral frameworks and exploring their applications in chiral-ligand synthesis and asymmetric catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation